PENGEMBANGAN OBJEK WISATA CANDI MUARA TAKUS DI KABUPATEN KAMPAR - eka Anggia Anglan; Rosyetti '; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
In today's world of tourism development, the type of tourism in Indonesia is environment based tourism (nature) and tourism based history. However, management and development in Indonesia is still lacking attention. One of these attractions Muara Takus located in Kampar regency. In a development needs to be carried out in depth study to determine the current situation and the development of effective strategies so that their potential can be utilized as much as possible. This research problem formulation is the development strategy of attraction in the village of Muara Takus. The purpose of this study was to determine the development strategy attractions Muara Takus in District XIII Koto Kampar regency. The method used in this research is SWOT analysis. SWOT Analysis is used to determine the situation of attraction Muara Takus to identify the internal and external factors that affect attraction. The results based on SWOT analysis showed attractions Muara Takus are in quadrant 1 with a intersection of 1.74; 1.18 where the situation can be done by having the opportunities and strengths that can take advantage of existing opportunities in order to enhance the growth of attraction Muara Takus. It describes the situation attraction Muara Takus in a position to support an aggressive strategy means in a favorable situation.Keywords : development strategy, attraction, SWOT Analysis